2020
DOI: 10.3389/fnhum.2020.609170
|View full text |Cite
|
Sign up to set email alerts
|

Neural and Genetic Bases for Human Ability Traits

Abstract: The judgement of human ability is ubiquitous, from school admissions to job performance reviews. The exact make-up of ability traits, however, is often narrowly defined and lacks a comprehensive basis. We attempt to simplify the spectrum of human ability, similar to how five personality traits are widely believed to describe most personalities. Finding such a basis for human ability would be invaluable since neuropsychiatric disease diagnoses and symptom severity are commonly related to such differences in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…Heritabilities of performance on the NIH Toolbox seem roughly on par with the results in adults (Pinto et al 2020 ), where general aggregate cognition metrics showed heritabilities around 50%, with individual task or cognitive factor score heritabilities generally lower. The findings are consistent with expectations for the composite measures of fluid and crystallized ability.…”
Section: Substantive Considerationssupporting
confidence: 63%
“…Heritabilities of performance on the NIH Toolbox seem roughly on par with the results in adults (Pinto et al 2020 ), where general aggregate cognition metrics showed heritabilities around 50%, with individual task or cognitive factor score heritabilities generally lower. The findings are consistent with expectations for the composite measures of fluid and crystallized ability.…”
Section: Substantive Considerationssupporting
confidence: 63%
“…Sensorimotor differences represent promising endophenotypes for ASD as they are highly quanti able, highly heritable [14,15], and evident in autistic individuals [16,17] and their unaffected relatives [18,19].…”
Section: Introductionmentioning
confidence: 99%